PENGARUH BEBAN KERJA, MOTIVASI, DAN INTEGRITAS TERHADAP KUALITAS AUDIT (STUDI PADA INSPEKTORAT KABUPATEN ACEH BESAR, ACEH BARAT DAYA, DAN KOTA BANDA ACEH) - Hasina, Amalya; Fitri, Fauziah Aida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
This study aims to determine the quality of the audit on the district inspectorate Aceh Besar, Aceh Barat Daya, and Banda Aceh through workload, motivation, and integrity. The data used in this study is primary data, the method of data collection is done by distributing questionnaires. Data obtained were analyzed using Linier Regression Techique with program IMB SPSS Ver 24. The result of analysis in this research is the working load has negatively significant impact to audit quality, to motivation and integrity was found to have positevly significant impact to audit quality inspectorate Aceh Besar, Aceh Barat Daya, and Banda Aceh.